PENGEMBANGAN VIDEO PEMBELAJARAN UNTUK MEMBACA AKSARA JAWA PADA PESERTA DIDIK KELAS IV SEKOLAH DASAR - Hani Aries Ikasanti; Nanang Khoirul Umam; Ismail Marzuki (JUSEDA, 2021)
The development research aims to know the validity of development learning video to read aksara Jawa for fourth grade elementary school student. The process of developing learning media video uses a modified and simplified 4-D model, namely, defining, designing, developing, and without disseminating. The result of the development is a learning video that contains Javanese materials. Data sources in this development research are material validator and media validator. Data collection used is a learning media validation. With data analysis, namely analyzing the validity of learning media. Based on the result of the data from validation, it was found that the development of learning video to read aksara Jawa fulfilled the worthy or good criteria, as follows: a) Learning media validation result the material validator gets 80% precentage wich is categorized as valid and can be used during the learning process, and b) Learning media validation result the media validator gets 73,33% precentage wich is categorized as valid and can be used during the learning process.